Estimation of Soaking Conditions for Edible Burdock in Preparing Low Potassium Diets - Naito, Hatsue (Eiyōgaku zasshi, 1991)
In preparing low potassium diets for renal failure patients, soaking conditions for edible burdock were studied. The soaking solution temperature and the vinegar concentration were studied. The following results were obtained. 1) Higher the solution temperature and the vinegar concentration, the higher the eluation ratio of potassium and calcium became. The higher the vinegar concentration, the higher the eluation ratio of phosphorus became. 2) Lye removal efficiency: Lye can be removed efficiently at the solution temperature of 30°C and the vinegar concentration of 0%. 3) Functional test: Functional test of stir-fried shredded burdock indicated that the higher K eluation ratio and suitably removed lye in order to obtain the dish with, the solution temperature should be about 30°C and the vinegar concentration about 1%.